2017
DOI: 10.3727/152599517x15073047237205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trade Show Environments on Visitors

Abstract: Tourism trade shows that are open to the public as well as to buyers and sellers are an emerging channel for the promotion of products to potential tourists. However, few studies have explored the influence of environmental stimuli on nonbusiness visitors' emotions. Moreover, the moderating effect of visitors' expectations remains understudied in the context of trade show management. To address this issue, this study reports on research derived from 611 respondents at a Taiwanese tourism trade show through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…The M-R model and its modifications have been applied in different contexts to examine the influence of environmental stimuli on consumers' evaluation of their consumption experiences and behaviors, such as retail (Ong & Khong, 2011), event management (Wong, Li, Chen, & Peng, 2017), restaurant management (Jang & Namkung, 2009), and tourist studies (Su & Hsu, 2013). For example, Wong et al (2017) confirmed the service staff quality, atmospherics, and information rate can affect trade show visitors' emotions, which, in turn, can affect their intentions to revisit and recommend. Additionally, Chen et al (2015) found diners' emotions are affected by the quality of food and drink, as well as the service staff quality, atmospherics, and their interactions with other customers.…”
Section: M-r Model and On-site Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The M-R model and its modifications have been applied in different contexts to examine the influence of environmental stimuli on consumers' evaluation of their consumption experiences and behaviors, such as retail (Ong & Khong, 2011), event management (Wong, Li, Chen, & Peng, 2017), restaurant management (Jang & Namkung, 2009), and tourist studies (Su & Hsu, 2013). For example, Wong et al (2017) confirmed the service staff quality, atmospherics, and information rate can affect trade show visitors' emotions, which, in turn, can affect their intentions to revisit and recommend. Additionally, Chen et al (2015) found diners' emotions are affected by the quality of food and drink, as well as the service staff quality, atmospherics, and their interactions with other customers.…”
Section: M-r Model and On-site Involvementmentioning
confidence: 99%
“…Scholars who have adapted the M-R model consider stimuli and behaviors that are relevant to their settings (Jang & Namkung, 2009;Wong et al, 2017). The present study focuses on the perceived experiential value of cultural tourism destinations.…”
Section: M-r Model and On-site Involvementmentioning
confidence: 99%
“…The service quality of the exhibition is a subjective evaluation of the visitors’ perception of the overall service provided by the exhibition organizers [ 32 ], which can be a key factor leading to the visitors’ future visit. The theory suggested by Zeithaml, Berry, and Parasuraman [ 33 ] that service quality affects customers’ favorable or unfavorable behavior has been found in exhibition research [ 34 , 35 , 36 , 37 , 38 ]. In particular, a study by Hakim, Zanetta, and Cunha [ 12 ] found that the perceived risk of COVID-19, disease denial, and health surveillance trust in restaurants influence the intention to revisit restaurants, which provides great implications for exhibition organizers.…”
Section: Literature Review and Research Question Developmentmentioning
confidence: 99%
“…This study incorporates consumers' expectations into the proposed framework as a moderating variable. In this study, expectations are what customers feel they should receive while staying in a luxury hotel (Wong et al 2017). The expectation/disconfirmation paradigm is one of the dominant models in consumer satisfaction research (Harrington et al 2011;Oliver 1980).…”
Section: Experiential Value and Expectationmentioning
confidence: 99%